Radiological Assessment of Femoral Bicondylar Angle among Persons Attending a Tertiary Health Care - Pradhan, Allin; Lama, CP; Dhungel, S; Ghosh, SK (Nepal Medical College Journal, 2019)
Femoral bicondylar angle is the angle between an axis through the shaft of the femur and a line perpendicular to the infracondylar plane. This study aims to assess femoral bicondylar angle measured from radiograph of femur and knee joints obtained from teaching hospitals in Kathmandu Nepal. Total of two hundred AP view radiograph of knee joint were collected, out of which, 50 each were of male right and left knee joint and 50 each were of female right and left knee joint. The mean angle for the right male femur was 7.86° with the range of 5°-10° and mean angle for the right female femur was 8.82° with the range of 6°-11°. On the left side, bicondylar angle ranged in male from 6° -10° with the average of 7.46° and in female range was 6°-11° and average was 8.66°. The bicondylar angle was higher in female on both the side, the difference was statistically significant on the left side (P=0.004) and significant on the right side (P=0.001). The finding of the study showed the femoral bicondylar angles were greater in right femur than left femur in both sexes. The difference in the bicondylar angle between the right and left femur was statistically insignificant in both sexes. (male p=0.144, female p=0.541). The result from this study has shown that femoral bicondylar angles were generally greater amongst the females as compared to the males; greater in right femur than left femur in both sexes.